Penerapan Sistem Informasi Raport Online - Pangastuti, Ayu Desy; Priantinah, Denies (Ekuitas: Jurnal Pendidikan Ekonomi, 2019)
Technological advancements make it easy for everyone related to the ease of getting and managing information. One concrete example is the development of the internet which has become an icon of technological development. Especially in the era of education 4.0, internet plays a very important role in the education process. In the education era 4.0 educators and students are required to be able to integrate technology in every educational activity. One application of technology in education today is the existence of a system of information on report cards based on the internet or what we are familiar with online report cards. This research is a literature study that aims to collect information relating to the use of online report card information systems that are applied by several schools. The results obtained from this literature study are online report cards that make it easy for educators to process student value data that can be accessed by both students and parents.